Peningkatan Prestasi Belajar Peserta Didik dengan Menggunaan Metode Demonstrasi Pada Proses Pembelajaran Rias Wajah - Sri Suswati (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
This study aims (1) to find out the demonstration method can improve students' learning achievement (2) to describe the process before and after the use of the demonstration method in daily makeup learning materials according to the design and theme (3) to measure the magnitude of the increase in achievement learn students by using the demonstration method. This study uses descriptive quantitative and qualitative demonstration methods. The research subjects were 32 students of class X Beauty Management 2 SMK Negeri 3 Bogor City, odd semester, 2017/2018 academic year. The technique used in this research is a practical test/examination and observation. The instruments used are learning outcomes test questions (practice) and observation sheets. The results of this study indicate that the ability of students to apply daily make-up practice through the use of the demonstration method can improve learning achievement and student activity. In addition, there is also an increase in learning achievement in the form of an increase in the average value of the class and an increase in the percentage of students' learning completeness. If we look at the increase in learning outcomes from cycle 1 to cycle II, there is an increase in learning mastery from 65.63% to 100%. there was an increase in the average value from 69 to 80.47. Thus, the learning achievement of students in class X Beauty Management 2 SMKN 3 Bogor in the daily make-up material according to the design and theme is declared complete. Therefore, researchers suggest that variations of learning methods are needed to avoid student saturation. One of them applies learning methods, especially demonstration learning methods. Keywords: Demonstration learning method can improve achievement learn students. Basic Beauty subject